The Areas of Applied Linguistics (Journal of Human Sciences, 2023)
A B S T R A C TThis paper is concerned with a fundamental issue of linguistics in general, and applied linguistics in particular, as it seeks to shed light on the nature of the relationship between the field of applied linguistics and the field of teaching and learning languages.In addition, it is preoccupied with highlighting the most important research areas that fall within the interests and concerns of applied linguistics, in addition to showing the importance of applied linguistics in advancing these areas, taking the example of the field of teaching and learning languages.Based on the foregoing, this paper attempts to answer many interrelated questions, such as:- What are the most prominent research areas that fall within the interests of applied linguistics? - To what extent does applied linguistics contribute to the development of these areas?